1993
DOI: 10.1159/000108681
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cerebrovascular Reactivity in Headache-Free Migraineurs

Abstract: The thermographic finding of a unilateral ''cold patch'' on the forehead of both classic and common migraine sufferers has prompted the suggestion that there is an asymmetry in the vasomotor tone of superficial extracranial arteries that could also be present in cerebral vessels. Transcranial Doppler sonography allows the study of the response of intracranial arteries to variations of blood pCO2, which may give an estimate of vasomotor tone regulation. Thirty headache-free migraineurs were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Others have also found an increased CVR in patients with migraine using different methods but they did not analyse patients with MA and MWOA separately, which makes a healthy comparison difficult (6, 7). On the contrary, studies reporting a normal (8, 9) or attenuated vasodilatory response (1012) also exist. The great differences in inclusion criteria, diagnostic techniques and timing of study with regard to the last migraine attack make it extremely difficult to pool the results obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also found an increased CVR in patients with migraine using different methods but they did not analyse patients with MA and MWOA separately, which makes a healthy comparison difficult (6, 7). On the contrary, studies reporting a normal (8, 9) or attenuated vasodilatory response (1012) also exist. The great differences in inclusion criteria, diagnostic techniques and timing of study with regard to the last migraine attack make it extremely difficult to pool the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Results of studies measuring cerebrovascular reactivity (CVR) in migraine interictally have also been contradictory. Most studies done on migraine without aura (MWOA) or migraine with aura (MA) showed a normal or increased CVR (6)(7)(8)(9), but studies showing a reduced vasodilatory response also exist (10)(11)(12). The discrepancies in these results can be explained by various factors, including time of measurement with regard to the last migraine attack, inclusion of both MA and MWOA as 'migraine' or differences in techniques used for measuring CVR (i.e.…”
Section: Introductionmentioning
confidence: 99%